KADAL IRAN (ETHANOL CONTENT NIRA SIWALAN (Borassus flabellifer)) WITH GC-MS (GAS CHROMATOGRAPHY MASS SPECTROMETRY) ANALYSIS - Ulfa, Maria; Astuti, Retno Yuni; Alam, Rizky Bachrul; Suharsanti, Ririn (Media Farmasi Indonesia, 2019)
There are many siwalan saplings among the people who utilize various kinds of fruit,leaves, nira siwalan. However, many people like the fruit and the water. In this case, legenlontar or other names nira siwalan can produce ethanol from siwalan flowers. So that, frommany people using nira only as a drink and so far some people produce nira on a small scale.Nira is a liquid that contains certain sugar levels, namely sucrose, glucose, fructose andcarbohydrates, which have an average acidity level of 6-7 and smell nice. This study aims todetermine the amount of ethanol content contained in nira siwalan and determine the effect ofstorage time on ethanol levels in nira siwalan. Samples of nira siwalan both original andbulk were fermented for 3 days, 6 days, and 9 days and then distilled at a temperature of78.37 ° C. Determination of ethanol content in the distillate results was carried out usingGCMS (Gas Chromatography Mass Spectrometry). The results of this study are the originalethanol content of nira siwalan at storage of 3.6.9 consecutive days, namely 0.27%, 0.91%,and 1.02%. While the results of the bulk ethanol juice of the siwalan level at storage of 3,6.9days were obtained ethanol levels respectively ie 32.05%, 39.99% and 44.42%. From thisstudy it can be concluded that the ethanol content in bulk nira siwalan is more than theoriginal nira siwalan.